Communicating a Protesting Protestant Heritage. Issue 3 (4th September 2017) - Rowe, Terra Schwerin
Abstract: This article opens by wondering, as many critics did during and after World War II, why a tradition named for its protesting impetus is today often marked by complacency and quietism. In conversation with political theorist William Connolly and Rev. Dr. William Barber's activism, this article suggests that Luther's unique articulation of the communicatio idiomatum might offer a compelling and coherent model for Lutheran ethical‐political agency that can provide an alternative to—rather than reinforcing—the modern isolated subject cum homo economicus often associated with idealized images of Luther's protest before the Diet of Worms.